2019
DOI: 10.1590/0103-8478cr20180353
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic acid combined with hand pollination increases ‘Red’ and ‘Lessard Thai’ sugar apple fruit quality and produced parthenocarpic ‘Gefner’ atemoya fruits

Abstract: The present research aimed to evaluate the effect of applying gibberellic acid (GA3) with hand (HP) or natural pollination (NP) on fruit set and the fruit quality of ‘Red’ and ‘Lessard Thai’ sugar apple and ‘Gefner’ atemoya fruits.This study was performed in an experimental orchard located in Homestead, Florida, USA. The experimental design included randomized blocks, with eight treatments, four replicates and four plants per plot. Treatments included: (1) HP; (2) HP + 10 mg L-1 GA3; (3) HP + 100 mg L-1 GA3; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…In general, the application of plant regulators did not affect fruit quality. Similar results were observed by Pereira et al (2019) with Annonaceae cultivars. In contrast, Verotti et al (2019) observed SS increases (°Brix) and pH reduction with the increase in concentration of plant regulator mix (auxin, cytokinin and gibberellin).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In general, the application of plant regulators did not affect fruit quality. Similar results were observed by Pereira et al (2019) with Annonaceae cultivars. In contrast, Verotti et al (2019) observed SS increases (°Brix) and pH reduction with the increase in concentration of plant regulator mix (auxin, cytokinin and gibberellin).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, Verotti et al (2019) observed SS increases (°Brix) and pH reduction with the increase in concentration of plant regulator mix (auxin, cytokinin and gibberellin). The produced fruit presented a standard organoleptic quality for the species, with physical and physicochemical characteristics similar to those of other studies (Moura et al, 2019;Pereira et al, 2014a;2014b;Pereira et al, 2019;Santos et al, 2016;.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Three applications of gibberellic acid at 500 ul L −1 plus hand pollination of Gefner atemoya resulted in larger fruit with fewer seeds and three applications of 1,500 ul L −1 of gibberellic acid alone produced seedless fruit of good quality (Santos et al., 2016). Similarly, ‘Red’ and ‘Lessard Thai’ sugar apple flowers treated with three applications of gibberellic acid (1,000 ul L −1 ) alone or with hand pollination resulted in high percent fruit set (≥90%) (Pereira et al., 2019). Gibberellic acid treatment plus hand pollination produced fruit that had similar fruit quality as hand pollinated only Red and Lessard Thai sugar apple fruit.…”
Section: Horticultural Characteristicsmentioning
confidence: 99%